Isotopic insights into the fate of atmospheric nitrogen in alpine tundra ponds with contrasting land cover and cryospheric conditions - R. Balestrini; N. Colombo; M. Freppaz; M.F. Lehmann; C. Delconte; E. Pintaldi; F. Salerno; I. Matiatos (CATENA, 2026)

Experimentally informed limit states and fragility curves of rocking blocks via shaking table tests - Carla Colombo; Georgios Vlachakis; Nathanaël Savalle; Anastasios I. Giouvanidis; Nuno Mendes; Paulo B. Lourenço (Bulletin of Earthquake Engineering, 2026)
This paper presents an extensive shaking table campaign conducted on free-standing rocking blocks subjected to recorded earthquakes. The campaign investigates different sources and degrees of variability in the rocking response, considering material irregularities, differences in block aspect ratios, and variability in the input ground motions. The experimental programme consists of the development of experimental incremental dynamic curves, incorporating test repetitions, thereby addressing the repeatability limitation of most experimental campaigns, resulting in a dataset of over 300 shaking table tests. The analysis of the results is organised in a three-stage framework. First, the rocking response is examined through a deterministic approach based on time-history analyses. Subsequently, a statistical evaluation is conducted to explore the experimental relationships between engineering demand parameter and selected intensity measures. Finally, the pronounced influence of various sources of uncertainty on the rocking response highlights the necessity of a probabilistic interpretation of the data, culminating in the development of experimentally informed fragility curves. This paper introduces a novel methodology for the objective identification of experimental limit states for rocking structures, proposing ranges for three response thresholds corresponding to limited rocking, moderate rocking, and near-collapse conditions that can be adopted for vulnerability assessments.

Insights on the experimental dynamic behaviour and energy losses of rocking blocks under free vibration - Carla Colombo; Georgios Vlachakis; Anastasios I. Giouvanidis; Nathanaël Savalle; Nuno Mendes; Paulo B. Lourenço (Bulletin of Earthquake Engineering, 2026)
This study focuses on the experimental response of free-standing hard limestone blocks under free vibration. The campaign includes 120 tests, varying the block’s height-to-width ratio and considering multiple specimens to account for the aleatoric variability of the phenomenon. The study offers full reconstruction of the three-dimensional free-rocking motion, giving insights into the influence of unintended geometrical asymmetries, as well as material and interface irregularities on the response. The paper revisits the experimental estimation of the angular Coefficient of Restitution (CoR) through different methodologies based on the angular velocities, potential energy, and potential and frictional energies. The results are compared with Housner’s theoretical model. Due to the sensitive nature of rocking motion, a statistical approach is employed. The findings indicate that Housner’s model provides statistically accurate predictions of energy losses for blocks of medium-to-high slenderness (i.e. with aspect ratio $$5 \le {H \mathord{\left/ {\vphantom {H B}} \right. \kern-\nulldelimiterspace} B} \le 10$$ while it becomes statistically inaccurate for very slender $${H \mathord{\left/ {\vphantom {H B}} \right. \kern-\nulldelimiterspace} B} > 10$$ and very stocky $${H \mathord{\left/ {\vphantom {H B}} \right. \kern-\nulldelimiterspace} B} < 5$$ blocks. Importantly, the study demonstrates that all three experimentally estimated CoRs statistically depend on the aspect ratio. Finally, the CoRs extracted from the potential energy and potential and frictional energies are found statistically dependent on the rocking amplitude, while the CoR extracted from the angular velocities show statistical independence. Overall, this study offers a pathway for more systematic analyses and improved predictions of energy losses during impacts.

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

The italian national genomic strategy: current status, challenges, and future perspectives in clinical practice and public health - Francesco Andrea Causio; Sara Farina; Alessandra Maio; Flavia Beccia; Luigi Russo; Valentina Baccolini; Matteo Chiara; Americo Cicchetti; Gualtiero I. Colombo; Giovanni Comandé; Domenico Coviello; Ruggero De Maria; et al. (Journal of Community Genetics, 2025)
This article presents the outcomes of a national initiative aimed at developing a technical document to support the future Italian National Genomic Strategy, carried out from 2021 to 2024 through the collaboration of 14 research institutions. The project was designed to align with major European genomic initiatives, particularly the “1 + Million Genomes” (1 + MG) Declaration and its supporting programs, including Beyond 1 Million Genomes (B1 + MG), the Genomic Data Infrastructure (GDI), and Genome of Europe (GoE). The initiative was structured around 12 National Mirror Groups (NMGs), each addressing a specific domain such as clinical implementation, ethical and legal issues, data governance, health economics, and public engagement. Through expert consensus and coordinated activities, the project produced a comprehensive technical document outlining seven strategic lines and related intervention areas. These include the integration of genomic testing into clinical practice, development of specialized genomic centers, creation of a national genomic data infrastructure, professional training, and public education. The proposed strategy emphasizes equitable access to genomic medicine, the use of health technology assessment to evaluate new technologies, and the importance of citizen engagement and literacy. By fostering collaboration among institutions, healthcare professionals, and the public, the final goal is to position Italy as a leader in genomic medicine and ensure the responsible, effective, and ethical use of genomics in public health and clinical care.

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

P25-21: Approach and challenges in the toxicological and allergenicity risk assessment of novel proteins and their sources - I. Nuin Garciarena; O. Albert; P. Colombo; A. Fernández Dumont; M. Laganaro; A. Muñoz González; E. Noriega Fernández; G. Precup; R. Roldán Torres; A. Rossi; E. Ververis; A. Germini; et al. (Toxicology Letters, 2023)

The impact of Li-bearing pegmatite mining on the dissolved geochemical signature of a mountain stream in the Pampean ranges, Central Argentina - Milagros Marqués; Andrea I. Pasquini; María Gabriela García; Verena A. Campodonico; Fernando Colombo; Diego M. Gaiero; Karina L. Lecomte (Sustainable Water Resources Management, 2023)

Colostrum quality associations with passive immunity transfer in foals - H B Magalhães; G Araujo; I Colombo; K M Spencer; G Podico; I F Canisso (Journal of Equine Veterinary Science, 2023)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Chronology of recent sedimentary infill of the Inner Río de la Plata Estuary, Argentina - Ferran Colombo; Jordi Serra; Patricia Cabello; José Bedmar; Federico I. Isla (Journal of Iberian Geology, 2021)
The Inner Río de la Plata Estuary is a sedimentary depositional system that resulted from fluvial-deltaic activity. Gentle Pliocene–Pleistocene slopes make-up the northern side of the estuary whereas small cliffs of the same age constitute the southern side. A long coastal estuarine barrier developed at about 6000 years BP when the maximum flooding surface occurred. Attached to this barrier, and at a lower elevation, is a large strandplain (covering an area of about 2400 km 2 ) which displays more than 220 beach ridges. In different areas, the dating indicates a periodicity of 13.4–13.7 years for the development of each beach ridge. These data are like the periodicity of the ENSO effects, which could be associated with the variability of Sunspots. These ridges were formed shortly after the maximum flooding surface, which was followed by a gradual fall in sea-level that contributed significantly to the Inner Río de la Plata Estuary sedimentary infill. In addition, ENSO activities were probably instrumental in the distribution of the main geoforms in the Inner Rio de la Plata Estuary. Small deltas, which were generated by other rivers and creeks such as the Nogoyá Arroyo and the Gualeguay River, developed coevally with the coastal estuarine barrier. The Ibicuy Delta grew in the middle of the inner Río de la Plata Estuary when the former Paraná River flowed northwards during the sea-level fall. The upper part of the delta front was reworked, giving rise to a large dunefield. Thereafter, a chenier plain developed along with tidal flats. The current Paraná Delta continues to prograde at a rate of about 56–64 m/year (m year −1 ). The sedimentary infill of the Inner Río de la Plata Estuary occurred along the Holocene.

Short-Term Effects of Genetically Modified Potato on Arbuscular Mycorrhizal Fungal Communities - Betina I. Stephan; Roxana P. Colombo; Vanesa A. Silvani; Mariana Pérgola; Alicia M. Godeas; Alejandro G. Pardo; Laura Fernández Bidondo (Journal of Soil Science and Plant Nutrition, 2019)

Pumice clasts in cross stratified basalt-dominated sandstones and conglomerates. Characteristics and depositional significance: Huarenchenque Fm (Neuquén, Argentina) - F. Colombo; R. Bargalló; L. A. Spalletti; P. Enrique; I. Queralt (Journal of Iberian Geology, 2019)

Effects of aerobic exercise training on metabolism of nitric oxide and endothelin-1 in lung parenchyma of rats with pulmonary arterial hypertension - A. Zimmer; R. B. Teixeira; J. H. P. Bonetto; R. Siqueira; C. C. Carraro; L. M. Donatti; A. Hickmann; I. E. Litvin; A. E. G. Godoy; A. S. Araujo; R. Colombo; Adriane Belló-Klein (Molecular and Cellular Biochemistry, 2017)

The relationship between carbonate facies, volcanic rocks and plant remains in a late Palaeozoic lacustrine system (San Ignacio Fm, Frontal Cordillera, San Juan province, Argentina) - P. Busquets; I. Méndez-Bedia; G. Gallastegui; F. Colombo; R. Cardó; O. Limarino; N. Heredia; S. N. Césari (International Journal of Earth Sciences, 2013)

Production of tannase from wood-degrading fungus using as substrate plant residues: purification and characterization - R. M. Ordoñez; I. Colombo; M. R. Alberto; M. I. Isla (World Journal of Microbiology and Biotechnology, 2011)

Identification of Moulds Belonging to the Penicillium Genus using a Polymerase Chain Reaction (PCR-SSCP) Method Followed by 'Computer Assisted' Statistical Analysis of the Electrophoretic Patterns - F. Colombo; L. Vallone; R. Capoferri; I. Dragoni (Veterinary Research Communications, 2003)